2002
DOI: 10.1098/rstb.2001.1050
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of phenotype in Trypanosoma brucei : a classical approach to potentially complex traits

Abstract: The genome of the African trypanosome, Trypanosoma brucei, is currently being sequenced, raising the question of how the data generated can be used to determine the function of the large number of genes that will be identified. There is a range of possible approaches, and in this paper we discuss the use of a classical genetic approach coupled with positional cloning based on the ability of trypanosomes to undergo genetic exchange. The genetics of these parasites is essentially similar to a conventional diploi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…In contrast, in the two MSH2 –/– cell lines, four of the five loci showed repeat length changes in at least one allele from the 10 clones examined and, in some cases, half or more of the alleles had changed size. The one locus that displayed no microsatellite instability in the MSH2 –/– cells, ChrII‐6 (Tait et al ., 2002; El Sayed et al ., 2003), was identified as 32 repeats of a CT dinucleotide on chromosome II in the T. brucei TREU927/4 genome reference strain. In the MITat1.2 cells used in this study, sequencing of the PCR products revealed that the loci had diverged to the extent that no contiguous CT dinucleotides longer than four repeats were present, almost certainly explaining its stability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in the two MSH2 –/– cell lines, four of the five loci showed repeat length changes in at least one allele from the 10 clones examined and, in some cases, half or more of the alleles had changed size. The one locus that displayed no microsatellite instability in the MSH2 –/– cells, ChrII‐6 (Tait et al ., 2002; El Sayed et al ., 2003), was identified as 32 repeats of a CT dinucleotide on chromosome II in the T. brucei TREU927/4 genome reference strain. In the MITat1.2 cells used in this study, sequencing of the PCR products revealed that the loci had diverged to the extent that no contiguous CT dinucleotides longer than four repeats were present, almost certainly explaining its stability.…”
Section: Resultsmentioning
confidence: 99%
“…Microsatellite PLC (El Sayed et al ., 2003) was amplified by 27 cycles of 95°C for 50 s, 58°C for 50 s and 70°C for 50 s using the primers PLCG (5′‐CAACGACGT TGGAAGAGTGTGAAC‐3′) and PLCH3 (5′‐CCACTGACCTT TCATTTGATCGCTTTC‐3′). Microsatellite ChrII‐6 (Tait et al ., 2002; El Sayed et al ., 2003) was amplified by 30 cycles of 95°C for 50 s, 52°C for 50 s and 72°C for 2 min using the primers ChrII‐6A (5′‐GTTGTGTGAGCAACGCAAGGGCGG‐3′) and ChrII‐6B (5′‐TATAACAACAGGTGAAGGAGAGGG‐3′). Microsatellites ChrI‐D2(7) and ChrI‐15 (Hall et al ., 2003) were amplified by 28 cycles of 95°C for 50 s, 54°C for 50 s and 68°C for 50 s using the primers ChrI‐7A (5′‐CCTGTTG GCCGCATTATTCGATGC‐3′) and ChrI‐7B (5′‐TGAGGAAGT GAGGGGAGACGGAAG‐3′), and ChrI‐15 A (5′‐TGGCTAGT TACACTGTAGTTCTCC‐3′) and ChrI‐15B (5′‐CCACAAC CACTCCTTGATATTCAC‐3′) respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Mice were housed in propylene cages with sawdust bedding and were fed on Harlan, SDS formula number I (Special Diet Services Ltd.) and drinking water supplemented with 0.05% paraminobenzoic acid (PABA) to aid parasite growth [14]. Temperature was maintained between 22 and 25°C with a 12 hour light/12 hour dark cycle.…”
Section: Methodsmentioning
confidence: 99%
“…Genetic work in human trypanosomatids has been limited by their diploidy and infrequent genetic or sexual exchange that has only been described in the insect host phase of African trypanosomes [29] and Leishmania [30]. Genomic data indicate that hybrids of various lineages of T. cruzi exist indicating that genetic exchange in this parasite can occur in nature, although infrequently.…”
Section: Trypanosomatidsmentioning
confidence: 99%